Stress and anxiety among people with type 2 diabetes mellitus - Jahan, Nasim; Kauser, Sharmin; Maruf, Mohammad Muntasir; Ahmad, Salma (BIRDEM Medical Journal, 2022)
Background: Diabetes mellitus and psychiatric disorders share a bidirectional association by influencing each other in multiple ways. The aim of the study was to find out proportion of persons having stress and anxiety and their association with age and gender among diabetic adult population. Methods: This was a cross-sectional study conducted among the patients attending the outpatient department of Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM General Hospital) and Dhaka Medical College & Hospital (DMCH) Dhaka, Bangladesh. By convenient sampling, 130 participants with type 2 diabetes mellitus were included according to inclusion and exclusion criteria during January-March, 2020. Data were collected through face-to-face interview by paper and pen method with a semistructured questionnaire. Dhaka University Anxiety Scale and Perceived Stress Scale-10 were used. Result: Most (87.7%) of the respondents had moderate level of anxiety. Severe stress was more prevalent among females (76.9%) than males (23.1%) and the difference was statistically significant (p=0.034). Twenty two (16.9 %) of respondents were above the cut off point for anxiety and 6.0% were female among them. Among the respondents with anxiety, male (81.8%) were more than female (18.2%) and the difference was significant (p=0.001). Stress was highly prevalent among comparatively younger age group (d”50 years) than the older (>50 years) and this difference was statistically significant (p=0.001). Anxiety was not significantly different among two age groups (p=0.183). Conclusion: Stress was more prevalent among females and younger age group. Anxiety on the other hand was more prevalent among males and there was no significant difference between older and younger age groups. Large scale and organized scientific studies in this field are needed to determine the effect of stress and anxiety in patients with diabetes mellitus. BIRDEM Med J 2022; 12(2): 136-141